(3YeOI GdMaGX aj JaSjQ CTQa GdCdaGXs - (3CMeO Hf jhSa Hf YHO GdOGje GdMdHj, CHh GdYHGS, TgGH GdOjf GdeYQha HGdSejf,J (B756 (3g` s
(3ChdgG (B:s
(3jHOC eG ajgG CKfGA eGOI (B( (3OQF(B) (3Hbhdg (B: (3eOGQGg GdfGS (B: (3Cf JdGjfge hdGJfaQge Yf faSc s
(3BNQgG (B:s
(3GdeYbOI (B: (3HQO ef HQhO gLQ Je HGH GdXGA hHJeGeg Je GdLRA GdKGfi hjJdhg cJGH GdYjf s
(3GdeNWhW ai ZQjH GdbQBf GdcQjes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B211s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B155 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs